Sisi personal dan tantangan digital: Kontrol diri dan perilaku phubbing pada ibu rumah tangga yang tidak bekerja (SUKMA : Jurnal Penelitian Psikologi, 2023)
The purpose of this study was to determine the relationship between self-control and phubbing behavior in non-working housewives. The population in this study included 103 non-working housewives. Participants in this study include housewives who do not work with at least 2 children, have smartphones and social media accounts and are 20-29 years old. The instruments in this study used the phubbing scale and self-control scale. This study uses a correlational quantitative method with purposive sampling technique. The data analysis method uses Spearman's Rho correlation analysis with the help of JASP 0.18.1.0, the results of the analysis show that there is a negative relationship between self-control and phubbing behavior, which means that housewives who have high self-control have low phubbing behavior, otherwise housewives who have low self-control have high phubbing behavior.